Monglish in post-communist Mongolia - Tankosic, Ana; Dovchin, Sender (WILEY, 2022)
This article examines the emerging language practice in post-communist Mongolia that we call ‘new Monglish’ – complex linguistic processes in which English may be deeply absorbed and integrated into the Mongolian language. The original forms of English have transformed as the Mongolian social media users manipulate English to function in the space of relocalisation – the linguistic process which is re-adapted to the local context to yield new local meanings. This English relocalisation process has adjusted to Mongolian alphabetical and grammatical systems and is yielding new meanings understandable only to the speakers of Mongolian. English has been integrated into the Cyrillic and transliterated Roman Mongolian scripts, full Mongolian sentences, and the Mongolian grammatical, phonetic, lexical, semantic, and syntactic systems. Such relocalisation of English makes it a part of the local language rather than a separate system.